1/3x-2=6-3/4x

Simple and best practice solution for 1/3x-2=6-3/4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/3x-2=6-3/4x equation:



1/3x-2=6-3/4x
We move all terms to the left:
1/3x-2-(6-3/4x)=0
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
Domain of the equation: 4x)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
1/3x-(-3/4x+6)-2=0
We get rid of parentheses
1/3x+3/4x-6-2=0
We calculate fractions
4x/12x^2+9x/12x^2-6-2=0
We add all the numbers together, and all the variables
4x/12x^2+9x/12x^2-8=0
We multiply all the terms by the denominator
4x+9x-8*12x^2=0
We add all the numbers together, and all the variables
13x-8*12x^2=0
Wy multiply elements
-96x^2+13x=0
a = -96; b = 13; c = 0;
Δ = b2-4ac
Δ = 132-4·(-96)·0
Δ = 169
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{169}=13$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(13)-13}{2*-96}=\frac{-26}{-192} =13/96 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(13)+13}{2*-96}=\frac{0}{-192} =0 $

See similar equations:

| 2(x+2)=3(x-7/8) | | q=8/15 | | 1.2x+6=3.6x+8 | | q=0,2 | | 5y-6/2=-y-9 | | 4x–3·(1–3x)=–3 | | X-5x+7+3=8x-7 | | 2x-11=-1-1.1x | | 180=16-w | | 3/7x+3=22 | | (12y+36)/(y-6)=1 | | 3y-10=y-38 | | 73-v=220 | | 6(2x-3)-4x=-26 | | 12+1/2(x+5)=2x+22 | | 6(2x-3)-6x=5 | | 289=240-w | | 2x+3(2x-6)=6 | | –3p–10=5 | | x÷6+x+2=x+11-5(4-x) | | 17+20+13w=20w−12 | | 172=58-y | | q2+1=50 | | –18d+8=–17d | | 2x+5=3x× | | n-18=-13 | | x+0.15x=7068 | | 9x+22=33x | | x+0.15x=240 | | M^3-4m-9=0 | | Z^3-4z-9=0 | | 88/4x+12=36/2x |

Equations solver categories